Performing in vitro sumoylation reactions using recombinant enzymes - Werner, Andreas; Moutty, Marie Christine; Möller, Ulrike; Melchior, Frauke (SUMO Protocols, 2009)
Sumoylation of proteins in vitro has evolved as an indispensable tool for the functional analysis of this post-translational modification. In this article we present detailed protocols for bacterial production of mammalian proteins necessary to perform in vitro sumoylation reactions, namely the E1 activating enzyme Aos1/Uba2 (SAE1/SAE2), the E2 conjugating enzyme Ubc9, SUMO-1 (identical protocols can be used for SUMO-2/3), and the catalytic domain of the E3 ligase RanBP2/Nup358. Two alternative procedures are described for the E1 enzyme, one depending on co-expression of His-Aos1 and untagged Uba2, and a second protocol for separate expression of His-Aos1 and Uba2-His and subsequent reconstitution of the active dimer. Two example conditions for in vitro sumoylation of RanGAP1 and Sp100 in the absence or presence of the SUMO E3 ligase RanBP2, respectively, are provided. Both protocols can be adapted easily to test in vitro conjugation of other target proteins and/or E3 ligases.